Analytical Study of Multi Stages Breast Cancer Mathematical Model Using Fractional Calculus (European Journal of Pure and Applied Mathematics, 2026)
In this manuscript, we investigate a mathematical model for breast cancer with chemotherapy treatment. Considered model is a six compartmental mathematical model for breast cancer having four stages of breast cancer, recovery and cardiotoxicity. Nonlocal fractional order derivative due to Caputo-Fabrizio is used for the considered study. The mentioned derivative has the ability to avoid singularity due to its nonlocal and nonsingular kernel. The considered model is investigated for qualitative analysis and also approximate solutions. Analysis is made on the basis of analytical method. Since breast reast cancer, is one of the most spreading cancer in the world which starts in the breast tissue. Type of breast cancer and overall health determine how it can be treated. Radiation, hormone therapy, chemotherapy, and surgery are among the available treatments. Usually, chemotherapy is used to treat it. Most chemotherapy drugs are quite effective at preventing cancer from spreading throughout the body. Chemotherapy, however, can result in cardiotoxicity due to its effects on blood arteries and heart muscle. A graphical presentation corresponding to some fundamental data is given via using MATLAB 2023.
Keywords: Epidemiological model; Multi stage breast cancer; Cardiotoxicity; CFFD; Laplace transform.